2014
DOI: 10.1002/ange.201404099
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Surface Engineering by a Conjugation‐and‐Release Approach Based on the Formation and Cleavage of Oxime Linkages upon Mild Electrochemical Oxidation and Reduction

Abstract: We report a strategy to rewire cell surfaces for the dynamic control of ligand composition on cell membranes and the modulation of cell-cell interactions to generate threedimensional (3D) tissue structures applied to stem-cell differentiation, cell-surface tailoring, and tissue engineering. We tailored cell surfaces with bioorthogonal chemical groups on the basis of a liposome-fusion and -delivery method to create dynamic, electroactive, and switchable cell-tissue assemblies through chemistry involving chemose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The interfacial oxime reaction is fast, chemoselective, occurs at physiological conditions (37 °C, pH 7) and requires no catalyst272829. Furthermore, the resulting oxime bond has no side reactions with biomacromolecules, is bio-orthogonal and therefore does not interfere with native biological processes30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial oxime reaction is fast, chemoselective, occurs at physiological conditions (37 °C, pH 7) and requires no catalyst272829. Furthermore, the resulting oxime bond has no side reactions with biomacromolecules, is bio-orthogonal and therefore does not interfere with native biological processes30.…”
Section: Resultsmentioning
confidence: 99%
“…These tissues may be used for many applications including drug screening and as models for disease and infection as well as eventual cardiac patch in vivo applications. Many different cell types including stem cells may be used with the strategy and the inter cell click ligation is compatible with microfluidic and 3D printing technologies2324252627282930. We believe the combination of liposome fusion, bio-orthogonal chemistry and cell surface engineering to tailor cell surfaces will have a significant impact on autocrine and paracrine signaling studies and for the development and evaluation of tissues for drug screening and therapeutic organ on a chip based biotechnology applications4041424344.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the density of aldehyde groups generated on the surface could be controlled by the exposure time using a mild oxidant (PCC) which flowed through the channels. Very recently, the same group used mild electrochemical oxidation and reduction chemistry to modify the surfaces of living cells by the use of a conjugation‐and‐release approach based on the formation and cleavage of oxime linkages . The strategy they described was based on hydroquinone‐containing molecules incorporated into cell walls, which were described as the “off state”.…”
Section: Oxime Ligationmentioning
confidence: 99%
“…Thus, a variety of targeting groups have been used to instigate fusion, 3,4 including small molecule based molecular recognition, 513 complementary DNA strands, 1424 peptides, 2533 metal complex formation, 3437 and complementary reactive functional groups. 3846 This process typically involves the incorporation of separate interacting functional groups into different vesicles to drive association as well as manipulation of the lipid content to dictate the stability of membrane bilayer and drive fusion.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 We and others have shown that the derivatization of intact liposomes can be conveniently achieved using bioorthogonal reactions, such as the copper-catalyzed azide-alkyne cycloaddition (CuAAC), 5156 the strain promoted alkyne-azide cycloaddition (SPAAC), 5759 and the Staudinger ligation. 60,61 This has been extended to the development of click chemistry-based membrane fusion systems using oxyamine-ketone 38,40,4446 as well as CuAAC 39,42 conjugations. The latter system suffers due to the delivery requirements and the toxicity and side reactions associated with the copper catalyst, 62 and since liposomes have been shown to decompose under CuAAC conditions.…”
Section: Introductionmentioning
confidence: 99%